ANALISIS KAPASITAS SUMBER DAYA MANUSIA, KEBIJAKAN PEMERINTAH DALAM PEMBERDAYAAN MASYARTAKAT LOKAL KABUPATEN MERAUKE - Syahruddin Syahruddin (EKONOMI & SOSIAL, 2018)
Community empowerment needs to be the main priority of the central government and regional governments, especially local people who live in villages far from remote villages, increasing community empowerment will improve welfare and sustainable development, through social culture, government policies, and human resource capacity. The purpose of this article is how the influence of government policy, human resource capacity on the empowerment of local communities in Merauke Regency, using the method of multiple regression analysis. The results of the study illustrate that the government program is very positive and significant, with a variety of program policies to the villages with various activities and financial assistance to the village. While the influence of community resource capacity is insignificant, there are still many local village communities that still lack education levels and health levels that are still high and socio-cultural which are still strong.